Risk of colorectal cancer in juvenile polyposis. Issue 7 (15th February 2007) - Brosens, Lodewijk A A; van Hattem, Arnout; Hylind, Linda M; Iacobuzio-Donahue, Christine; Romans, Katharine E; Axilbund, Jennifer; Cruz-Correa, Marcia; Tersmette, Anne C; Offerhaus, G Johan A; Giardiello, Francis M
Abstract : Background: Juvenile polyposis (JP) is an autosomal-dominant syndrome characterised by the development of hamartomatous gastrointestinal polyps and is associated with colorectal cancer. However, the relative and absolute risk of colorectal malignancy in these patients is not known. Methods: The incidence rates of colorectal cancer in patients with JP were compared with that of the general population through person-year analysis with adjustment for demographics. Results: In patients with JP, the RR (95% CI) of colorectal cancer was 34.0 (14.4 to 65.7). Similar risks were noted in both males (30.0, 9.6 to 68.6) and females (43.7, 8.8 to 125). The cumulative life-time risk for colorectal cancer was 38.7%. The mean (SD) age of diagnosis of colorectal cancer was 43.9 (10.4) years. Other gastrointestinal malignancies were not noted in this cohort. Conclusion: Patients with JP have a markedly increased RR and absolute risk for colorectal cancer and require vigilant colorectal surveillance starting at young age. A low threshold for recommending surgery with consideration for removal of the entire colorectum seems warranted.